"Securing the Rational Foundations of Human Living:" The Pedagogical Nature of Human Law in St. Thomas Aquinas. (2nd August 2014) - Jones, Brian
Abstract Every form of government, whether by its action or inaction, encourages certain forms of behavior and discourages others. The moral well being of a society necessitates its consideration of civil law's legitimate role in shaping moral character. In this paper, I will attepmt to argue that the Thomistic account of civil law is not merely negative, but entails a positive pedagogy that seeks to nurture the moral virtue of its citizens, for both the viciously inclined and those who are already good. Furthermore, Aquinas' theory of the common good is such that its role is not merely limited, i.e., through establishing some form of civic tranquility and providing basic goods of the material or economic order with little worry of the moral habits thus cultivated. The treatment of Thomas' teaching on human law will not be fully exhausted in this paper. However, from examining the texts from the Summa Theologiae and the De Regno, it will appear evident that St. Thomas has provided a concise and intelligent framework for seeing and actualizing the necessary relationship between human law and moral virtue.